Perhitungan Kecepatan Kendaraan Secara Otomatis Menggunakan Metode Frame Difference Berbasis Raspberry Pi - Faris Chandra Febrianto; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The variation of transportation which can be a helper for moving from another place is a part of technology advances. There are many of this transport who attracted the rider itself, with more and more variation vehicle user, sometimes increasing the trespasser of the road. These trespasser can be risk to other rider and increase crash incident, in the public road or freeway. The driver is also able to drive vehicles with different speeds but, many driver mostly do not care with speed limit that already shown clearly. From the explanation above, writer have an idea to make an artifact that does not can be used as CCTV but can known by the vehicle speeds automatic. This study about using frame difference method to detect an object by looking for differences from foreground with background, can resulting detect moving vehicles with an accurate average 90,1%. The advances of this method is only used grayscale color for processing image so it won't burden while processed. For the testing result about vehicle speeds, system has average error by 89,58% with program execution for system to run single video is 10,9 seconds.